Insights into medication adherence among Jordanian patients with dyslipidemia: evaluating health literacy, well-being, and doctor-patient communication - Muna Barakat; Samar Thiab; Shaymaa B. Abdulrazzaq; Marah Al-Jamal; Fotoh AlHariri; Rakan Bassam Ammari; Sara Mansour; Sami El Khatib; Souheil Hallit; Basile Hosseini; Diana Malaeb; Hassan Hosseini (Taylor & Francis Group, 2024)
Background: This study aimed to assess medication adherence among Jordanian patients with dyslipidemia and evaluate the impact of health literacy, well-being, and doctor-patient communication on adherence in this population. Dyslipidemia is a prevalent condition that significantly increases the risk of cardiovascular diseases, and understanding the factors influencing medication adherence is crucial for improving patient outcomes.Methods: An observational cross-sectional study was conducted from March to July 2023. A convenience sample of adult Jordanians diagnosed with dyslipidemia was surveyed in a tertiary hospital using validated scales: the Lebanese Medication Adherence Scale-14 (LMAS-14), the Doctor-Patient Communication Scale (DPC), the WHO well-being index, and the health literacy scale. Bivariate analysis and linear regression models were employed to analyze associations.Results: Among 410 participants (mean age 58.62 ± 12.11 years), the mean scores were LMAS-14 (35.10), DPC (55.77), WHO well-being (47.53), and health literacy (38.96). Higher medication adherence was associated with older age (B = 0.093, p = 0.049), university education (B = 2.872, p = 0.017), prior surgery (B = 2.317, p = 0.021), medium income level (B = 3.605, p = 0.006), and better doctor-patient communication (B = 0.166, p = 0.003). Conversely, cigarette smoking (B = −3.854, p = 0.001) and health insurance (B = −2.146, p = 0.039) were linked to lower adherence.Conclusion: The findings underscore the substantial interplay of socio-demographic and clinical factors affecting medication adherence. Enhanced public health interventions focusing on improving health literacy, communication quality, and addressing socio-economic conditions are vital for better adherence and patient outcomes in Jordan.